Perencanaan Arsitektur Enterprise Menggunakan Metode Enterprise Architecture Planning Studi Kasus: Kantor Sekretariat Majelis Rakyat Papua - Wellem Dysbert Yobi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract In the current era of information technology, organizations require the use of information technology to support business processes and strategic plans. One of the organizations that require the use of information technology is the Secretariat of the Papuan People's Council. However, in carrying out its duties, the MRP Secretariat has not maximally utilized information technology so that the data it has is still stored manually (paper-based), so the development of information technology is needed. In this case, the method used in Enterprise Architecture Planning. This method is used to describe the current condition of the organization and design the right enterprise architecture to achieve the organization's business goals in the future. This research produces three recommendations consisting of 9 data entities, 4 applications, and technology architecture planning for the MRP secretariat office. These three recommendations can then be used as a reference for the development and development of enterprise architecture in the MRP secretariat office in the future.